Obtaining a coffee-flavored dairy drink using soy milk and whey (Nexo Revista Científica, 2023)
A dairy drink was obtained by mixing the raw materials whey, cow's milk and soy milk. The products to be used in the formulation of the beverages were characterized physically-chemically. A  factorial design was carried out, where the levels of starch and whey were established. For this, the sugar concentration was fixed in the formulation of each of the experimental runs and the rest was completed with the whole cow's milk and soy milk components mixed in a 7/3 ratio. The best evaluated formulation was developed on a pilot scale and characterized. In the case of 1.2% starch, regardless of the whey content in the formulations, better results were always obtained. It was appreciated that the sensory quality of the product is conditioned by both the viscosity and the milky taste. The best evaluated formulation by the tasters was the one containing 1.2% starch and 30% whey. The sensory characterization of the beverage showed excellent quality, due to the perception of a correct combination of coffee flavor, soy flavor, and milk flavor. It presented a total solids content of 17.8% and an acidity of 0.07%.